Factors that affect the turnover intention among employees of non-nursing department in Mahkota Medical Centre, Melaka / Nur Hazwani Ahmad - Ahmad, Nur Hazwani (Faculty of Business and Management, 2014)
This study conducted to identify the factors that affect the turnover intention among employees in Mahkota Medical Centre, Melaka. Researcher has listed three variables which are performance appraisal and promotion, personality issues and pay and benefits as the independent variables and turnover intention as the dependent variable. The researcher distributed 191 sets of questionnaires to respondents which are the staff from non-nursing departments of MMC. The finding and analysis were made based on Statistical Package for Social Science (SPSS) version 20.0 to analyze the data. The finding of this study proves that only performance appraisal and promotion affects negatively to the turnover intention and it appear to be the most influenced factor towards the turnover intention among non-nursing staff in MMC.